Transportation of heat through Cattaneo-Christov heat flux model in non-Newtonian fluid subject to internal resistance of particles - Khan, M. I.; Alzahrani, F. (Applied mathematics and mechanics, 2020)
Thermal conduction which happens in all phases (liquid, solid, and gas) is the transportation of internal energy through minuscule collisions of particles and movement of electrons within a working body. The colliding particles comprise electrons, molecules, and atoms, and transfer disorganized microscopic potential and kinetic energy, mutually known as the internal energy. In engineering sciences, heat transfer comprises the processes of convection, thermal radiation, and sometimes mass transportation. Typically, more than one of these procedures may happen in a given circumstance. We use the Cattaneo-Christov (CC) heat flux model instead of the Fourier law of heat conduction to discuss the behavior of heat transportation. A mathematical model is presented for the Cattaneo-Christov double diffusion (CCDD) in the flow of a non-Newtonian nanofluid (the Jeffrey fluid) towards a stretched surface. The magnetohydrodynamic (MHD) fluid is considered. The behaviors of heat and mass transportation rates are discussed with the CCDD. These models are based on Fourier’s and Fick’s laws. The convective transportation in nanofluids is discussed, subject to thermophoresis and Brownian diffusions. The nonlinear governing flow expression is first altered into ordinary differential equations via appropriate transformations, and then numerical solutions are obtained through the built-in-shooting method. The impact of sundry flow parameters is discussed on the velocity, the skin friction coefficient, the temperature, and the concentration graphically. It is reported that the velocity of material particles decreases with higher values of the Deborah number and the ratio of the relaxation to retardation time parameter. The temperature distribution enhances when the Brownian motion and thermophoresis parameters increase. The concentration shows contrast impact versus the Lewis number and the Brownian motion parameter. It is also noticed that the skin friction coefficient decreases when the ratio of the relaxation to retardation time parameter increases.